Homossexualidade e envelhecimento : percepções e significados na trajetória na vida e no viver de homens e de mulheres - Cunha, Luciana de Almeida da (2021)
Introduction: Vulnerability is an extremely relevant topic to be addressed in various conditions associated with people's lives and lives. Vulnerability can generate, on an individual or collective level, inequalities and discrimination. Objective: To identify possible vulnerabilities involved in the aging process of homosexual people and the repercussions resulting from this association. Method: Semi-structured interviews were conducted with groups of homosexual and heterosexual elderly, male and female. Mixed methods were used to evaluate the data obtained. Results: The results of the study demonstrate that the groups of elderly homosexuals and heterosexuals have many characteristics in common. But in others it is possible to identify peculiar characteristics. Self-esteem was highlighted only in the group of elderly heterosexuals, and stigma, difficulty in accepting and prejudice against sexuality in the group of elderly homosexuals. Conclusions: Stigma and prejudice in relation to sexuality were more prevalent among elderly homosexuals, while prejudice in relation to age was more prominent among heterosexual elderly. These vulnerabilities suggest the need for adequate preparation of health professionals who serve this segment of the population, with a view to providing additional protection strategies